INTEGRATION PROCESSES AND THEIR EFFECT ON IMMIGRATION POLICY - V. Zlenko; A. Ryazantsev (Вестник университета, 2017)
The article deals with theoretical aspects of correlation between integration and immigration processes. After the research of current theoretical background related to the international economic integration the authors believe that the so-called triad «integration processes - waves of innovation - migration processes» should be examined individually. That is to say, the dynamics of an inheriting wave of innovation is consistent with the mobility of correlation between scarcity and redundancy of labour supply. This implies expediency of the regulatory action on these processes, including the implementation of the selective immigration policy and reasonable emigration policy, which may be either confirmed or rejected in an econometric framework, making it possible to trace the correlation of the immigration processes and performance of GDP in individual countries, members of integration associations.